Effects of Dietary Yeast, Saccharomyces cerevisiae, and Costmary, Tanacetum balsamita, Essential Oil on Growth Performance, Digestive Enzymes, Biochemical Parameters, and Disease Resistance in Nile Tilapia, Oreochromis niloticus - Hossein Adineh; Morteza Yousefi; Basim S. A. Al Sulivany; Ehsan Ahmadifar; Mohammad Farhangi; Seyyed Morteza Hoseini (Aquaculture Nutrition)
The present study assessed the effects of dietary yeast, Saccharomyces cerevisiae, and costmary, Tanacetum balsamita, essential oil on growth performance, biochemical parameters, and disease resistance of Nile tilapia, Oreochromis niloticus. Four diets containing 1 g/kg yeast (Sc), 0.1 g/kg costmary essential oil (Tb), 1 g/kg yeast + 0.1 g/kg costmary essential oil (Sc + Tb), and without Sc and Tb (control) were formulated and fed (2.5% per day) to triplicate groups of fish (average: 9.8 g; SD : 0.12) for 8 weeks. Each replicate was a 70-L tank, stocked with 25 fish. Then, the fish were intraperitoneally challenged by Aeromonas hydrophila, and blood samples were taken from the fish before and 12 hr postinfection. All experimental groups showed significantly higher growth performance and feed efficiency, compared to the control, and the highest values were related to Sc + Tb treatment (P <0.001). Sc group showed significant elevations in the intestinal amylase, lipase, and protease activities, but Tb group showed only elevation in lipase activity. The highest amylase (P=0.026), lipase (P=0.036), and protease (P=0.009) activities were observed in Sc + Tb treatment. The postchallenge survival of Sc (70.0%), Tb (73.3%), and Sc + Tb (76.6%) treatments were significantly (P=0.038) higher than the control (56.6%). Bacterial challenge significantly increased plasma cortisol, glucose, malondialdehyde, glutathione peroxidase, and superoxide dismutase, but decreased lysozyme, alternative complement, albumin, globulin, and catalase (P <0.001). The Tb treatment showed improvements in plasma antioxidant, immunological, and biochemical parameters, compared to the Sc treatment. The Sc + Tb treatment showed the highest albumin, globulin, lysozyme, total immunoglobulin, alternative complement, glutathione peroxidase, and superoxide dismutase, but the lowest cortisol, glucose, malondialdehyde, and catalase, before/after the challenge (P <0.001). In conclusion, dietary Sc + Tb supplementation positively affects growth performance, antioxidant, and immunological responses, thereby augments resistance of Nile tilapia to A. hydrophila infection.